Official Responses to Dealing with the Past in Northern Ireland: Between Remembering and Forgetting - Fabrice MOURLON (E-REA)
Since the early 2000s, Northern Ireland society has been considering whether it should confront its violent past. The voluntary sector and both the British and devolved governments have consulted the population on the issue. These surveys have concluded that part of the population was in favour of some mechanism to deal with the past. However no real consensus existed on a global process that would involve society as a whole. At the same time, the British government set up new Inquiries into controversial past events such as Bloody Sunday and established units within the police service to re-examine unsolved cases. In the absence of a global process to deal with the past such as the South African Truth and Reconciliation Commission, conclusions of these Inquiries and investigations have been made public since 2010. The analysis of some of these reports will reveal to what extent the truth about those past events has been established and responsibilities attributed and whether they offer an approach to remembrance that transcends the conflicts of the past..